Potential of plastic-based waste in geomaterial stabilization, grouting, and geotechnology applications: retro and prospective insights - Mary C. Ngoma; Jason Lin; Oladoyin Kolawole; Vincent O. Ogunro (Discover Civil Engineering)
Abstract Plastic-based materials, made from synthetic or semi-synthetic polymers, are extensively used in geotechnical engineering to stabilize geomaterials through geopolymers and geotextiles. Despite their convenience and versatility, their non-biodegradable nature poses challenges. Typically, plastic waste is recycled or repurposed for construction, asphalt modification, soil stabilization, geosynthetic materials, and transportation-related geotechnology applications. Although there have been advancements in recycling and reuse, no comprehensive review has explored the potential of plastic-based waste to enhance civil infrastructure. This study systematically reviewed how plastic-based material wastes can improve the engineering properties and resilience of geomaterials and civil infrastructures, highlighting the benefits and challenges of integrating these polymer-based wastes as grouts. It also addresses the environmental implications and strategies to mitigate negative impacts. The review findings indicate that the effectiveness of plastic-based materials depends on their type, shape, and quantity, influencing their use in geo-engineering as stabilization, replacement, and reinforcement agents. Using 0.5% plastic waste in pavement can eliminate 240,000 tons of waste annually, about 2.4% of the total plastic waste produced in the United States. This study further provides insights into the current application and future potential of plastic-based materials and waste in civil infrastructure, suggesting they cannot fully replace traditional construction practices due to their physico-hydro-chemo-mechanical properties but can enhance sustainability and resilience. Additionally, the study proposes a novel approach for plastic-based material waste disposal and/or storage in underground geological sequences (weathered bedrock or deep rock formations) as an alternative geotechnique for long-term plastic waste disposal management, offering a potential solution for grouting underground infrastructure.